Late clinical failure associated with cytochrome b codon 268 mutation during treatment of falciparum malaria with atovaquone–proguanil in traveller returning from Congo - Laurencie Massamba; Marylin Madamet; Nicolas Benoit; Alicia Chevalier; Isabelle Fonta; Véronique Mondain; Pierre-Yves Jeandel; Rémy Amalvict; Pascal Delaunay; Joel Mosnier; Pierre Marty; Christelle Pomares; et al. (Malaria Journal, 2020)
Abstract Background The drug combination atovaquone–proguanil, is recommended for treatment of uncomplicated falciparum malaria in France. Despite high efficacy, atovaquone–proguanil treatment failures have been reported. Resistance to cycloguanil, the active metabolite of proguanil, is conferred by multiple mutations in the Plasmodium falciparum dihydrofolate reductase (pfdhfr) and resistance to atovaquone by single mutation on codon 268 of the cytochrome b gene (pfcytb). Case presentation A 47-year-old female, native from Congo and resident in France, was admitted in hospital for uncomplicated falciparum malaria with parasitaemia of 0.5%, after travelling in Congo (Brazzaville and Pointe Noire). She was treated with atovaquone–proguanil (250 mg/100 mg) 4 tablets daily for 3 consecutive days. On day 5 after admission she was released home. However, many weeks after this episode, without having left France, she again experienced fever and intense weakness. On day 39 after the beginning of treatment, she consulted for fever, arthralgia, myalgia, photophobia, and blurred vision. She was hospitalized for uncomplicated falciparum malaria with a parasitaemia of 0.375% and treated effectively by piperaquine–artenimol (320 mg/40 mg) 3 tablets daily for 3 consecutive days. Resistance to atovaquone–proguanil was suspected. The Y268C mutation was detected in all of the isolates tested (D39, D42, D47). The genotyping of the pfdhfr gene showed a triple mutation (N51I, C59R, S108N) involved in cycloguanil resistance. Conclusion This is the first observation of a late clinical failure of atovaquone–proguanil treatment of P. falciparum uncomplicated malaria associated with pfcytb 268 mutation in a traveller returning from Congo. These data confirm that the Y268C mutation is associated with delayed recrudescence 4 weeks or more after initial treatment. Although atovaquone–proguanil treatment failures remain rare, an increased surveillance is required. It is essential to declare and publish all well-documented cases of treatment ...